Examining the Association Between Personal Victimization in Adolescence and Intimate Partner Victimization in Adulthood - Rima, Dzhansarayeva (International journal of offender therapy and comparative criminology, 2019)
A large body of research has examined various issues related to repeat victimization, including potential risk factors and theoretical explanations. Despite the amount of studies dedicated to focusing on repeat victimization, there are some notable gaps in the literature. One particularly noteworthy omission in this research is whether there is a link between personal victimization in adolescence and intimate partner violence (IPV) victimization in adulthood. The current study sought to address this gap. To do so, data drawn from the National Longitudinal Study of Adolescent to Adult Health were analyzed. The results revealed a statistically significant and relatively consistent association between personal victimization in adolescence and IPV victimization in adulthood. This association was detected for both males and females, and it was detected even after controlling for low self-control (males and females) and being the perpetrator of IPV (males). We conclude by noting some of the implications of these findings, as well as limitations to the study that need to be addressed in the future.